“I want to work for my people” – Towards a Specific Model for Indigenous Work-integrated Learning - Duder, Elisa; Foster, Erana; Hoskyn, Katharine (Work-Integrated Learning New Zealand (WILNZ), 2022)
This paper discusses changes taking place in the delivery of work-integrated learning (WIL) in a Faculty of Māori and Indigenous Development in Auckland, New Zealand. WIL in the faculty utilized a model adopted from a business school which did not recognize key aspects of the students’ lives and expectations, in particular the strong connection that Māori students can have with their communities. Over time the nature of the WIL experience is moving to a model based on Māori values. Indigenous models must be relevant to and driven by a community’s underlying values, as many students feel primary responsibility to their community, and second to the academy. This paper is part of an ongoing reflection on how WIL placements in Te Ara Poutama at Auckland University of Technology can fulfil wide-ranging expectations of students and their communities and help develop a coherent Indigenous framework for WIL.
Keywords: indigenous work-integrated learning; Māori; business studies; community